KONTRIBUSI KETERAMPILAN MEMBACA APRESIATIF TEKS CERPEN TERHADAP KETERAMPILAN MENULIS TEKS CERPEN - Hafizah, Tuti; R., Syahrul; Ratna, Ellya (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this study is to describe the contribution of reading skills to appreciate the short story text writing skills of short story students in grade XI SMA Negeri 5 Bukittinggi. The data of this research is score of reading skill test result of appreciation of short story text and score of skill text writing skill test result. The collected data is analyzed according to the indicators to score and score the students. The instrument of this study is an objective test for the appreciative skills of reading short story text and performance tests for short story text writing skills. Based on the result of the research, it is concluded that the skill reading comprehension skills of the short stories contribute significantly to the skill of writing the short story of the students of grade XI SMA Negeri 5 Bukittinggi on the n-1 freedom degree (56-1 = 55) and 95% significant level. Kata kunci: kontribusi, membaca apresiatif, menulis, teks cerpen